The fate of silent gods - Drakeford, Scott (Drakeford, Scott. Age of Ire, 2024)
"The Age of Ire saga continues with The Fate of Silent Gods, continuing the gripping, personal vengeance with compelling characters in a struggle for power. Emrael Ire has won the first round of war against the dark god, but at a terrible cost to himself. Unsure of who he can trust, even among his own people, Emrael must find a way to score a major victory against both the forces of the dark lord and the corrupt lords of the provinces. He thought he already paid his price. The gods will exact another. Age of Ire Rise of the Mages The Fate of Silent Gods"--